Increasing physical activity and decreasing sedentary activity in adolescent girls - The Incorporating More Physical Activity and Calcium in Teens (IMPACT) study - Hergenroeder Albert; Kelder Steven H; Hoelscher Deanna M; Jones Desiree; Sharma Shreela V (BMC, 2008)
Abstract Background Lack of regular physical activity and consequent sub-optimal bone mass acquisition in youth has been implicated as a primary cause of adult-onset osteoporosis. IMPACT was a behavioral theory-based 1 1/2 year randomized controlled field study aimed at increasing bone accretion in middle school girls. The objective of this study was to determine the intervention effects of the IMPACT program upon key physical and sedentary activity endpoints among schools that participated in the IMPACT study. Endpoints examined included weight bearing physical activity (WBPA); moderate to vigorous physical activity (MVPA); vigorous physical activity (VPA); MET (metabolic equivalent) - weighted WBPA and MVPA; sedentary activity; before/after-school physical activity; and weekend physical activity. Methods Primary data analysis using a pretest-posttest control group design was conducted utilizing mixed model analysis of covariance. Data gathered from the IMPACT cohort from 2000-2002 were analyzed to determine baseline versus follow-up differences in activity endpoints. Confounders investigated included ethnicity, body mass index, menarcheal status, participation in 7th grade PE/athletics, friend/familial support and neighborhood safety. Results Follow-up means were higher for participating intervention schools relative to control schools for all physical activity variables but were statistically significant only for the following variables: daily minutes of vigorous physical activity (mean difference between Intervention (I) and Control (C) = 6.00↑ minutes, 95% CI = 5.82-6.18, p = 0.05), daily after school activity minutes (mean difference between I and C = 8.95↑ minutes, 95% CI = 8.69-9.21, p = 0.04), and daily weekend activity minutes (mean difference between I and C = 19.00↑ minutes, 95% CI = 18.40-19.60, p = 0.05). The intervention significantly reduced duration of student daily TV/Video watching (mean difference between I and C = 12.11↓ minutes, 95% CI = 11.74-12.48, p = 0.05) and total daily sedentary activity minutes (mean difference between I and C = 16.99↓ minutes, 95% CI = 16.49-17.50, p = 0.04). Conclusion A well designed and implemented school based health and physical activity intervention can result in a positive influence upon increasing physical activity levels and decreasing sedentary activity. Future interventions should consider a more structured intervention component to obtain significant changes in WBPA.